2014
DOI: 10.1007/s00520-014-2503-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical approach in the management of oral chronic graft-versus-host disease (cGVHD) in a series of specialized medical centers

Abstract: The responses described the common practices for oral cGVHD in several specialized centers across the world. The choice of topical treatments was influenced by the availability of medications in the provider's country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…All patients undergoing HSCT should receive specific care, particularly those who develop cGVHD. A complete dental evaluation should occur regularly, and special attention should be focused on early detection of oral cancer and precursor lesions [ 14 , 17 , 18 , 28 ]; diagnosis and treatment of mucosal lesions [ 14 , 28 ] and erythema or lichen-type features with symptomatology [ 18 ]; caries prevention [ 14 , 28 , 29 ]; reestablishment of oral health in case of rampant caries [ 14 , 30 ], with the possibility of use of fluoride applications [ 14 ] or silver diamine fluoride for disease control and relief of hypersensitivity [ 30 ]; and pharmacological treatment [ 14 , 28 , 31 ] or nonpharmacological treatment [ 14 , 28 , 29 ] of hyposalivation and xerostomia.…”
Section: General Considerations Regarding Dental Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients undergoing HSCT should receive specific care, particularly those who develop cGVHD. A complete dental evaluation should occur regularly, and special attention should be focused on early detection of oral cancer and precursor lesions [ 14 , 17 , 18 , 28 ]; diagnosis and treatment of mucosal lesions [ 14 , 28 ] and erythema or lichen-type features with symptomatology [ 18 ]; caries prevention [ 14 , 28 , 29 ]; reestablishment of oral health in case of rampant caries [ 14 , 30 ], with the possibility of use of fluoride applications [ 14 ] or silver diamine fluoride for disease control and relief of hypersensitivity [ 30 ]; and pharmacological treatment [ 14 , 28 , 31 ] or nonpharmacological treatment [ 14 , 28 , 29 ] of hyposalivation and xerostomia.…”
Section: General Considerations Regarding Dental Treatmentmentioning
confidence: 99%
“…The diagnosis of oral cGVHD depends on the patient's history, clinical findings, and early signs and symptoms [ 14 ] and it is generally not necessary to perform a biopsy [ 28 ].…”
Section: General Considerations Regarding Dental Treatmentmentioning
confidence: 99%
“…There was a heterogeneity regarding the trial outcomes and outcome assessment and the mixed study design hindered gathering the studies for statistical analysis. It is acknowledged for most practitioners that topical corticosteroids are the first line of treatment for oral cGVHD [ 1 , 4 , 14 ]. Upon evaluation of the available evidence we agree on the net benefit of topical corticosteroids with a recommendation to “probably” the use of topical steroid is effective in management of signs and symptoms of oral mucosal GVHD with minimal easily avoided side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The review could not make recommendations regarding any topical intervention in oral cGVHD. Another study [ 14 ], a clinical survey, was conducted assessing clinical interventions for diagnosis and management of oral cGVHD. They reported that topical corticosteroids were the first line of treatment chosen by oral specialists.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentre questionnaire undertaken by Elad et al . ( 31 ) regarding the treatment of oral cGVHD showed that steroids were the first-line topical management of choice (91.7 %). The topical steroids budesonide (3mg/10ml) and dexamethasone (0.1mg/5ml) were the most commonly studied.…”
Section: Discussionmentioning
confidence: 99%